STUDI PENENTUAN PRODUKTIVITAS DANAU BUATAN DENGAN MEI (MORPHOEDAPHIC INDEX) ANALYSIS - Santoso, Arif Dwi (Jurnal Hidrosfir Indonesia, 2008)
The morphoedaphic index (MEI) has been used globally as a fish-yield estimator with widely divergent results. The fandamental concept of the MEI embraces standard thermodynamic theory, that of matter ( natrients) transported by energy within an open system. Of the three morphometric factors considered mean depth ,volume and area. The MEI is a reasonable compromise between unmanageable complexity and ecologic over simplification. Even so, its appropriate application presupposes both a fisheries and a limnological expertise, a rare disciplinary combination in those workers who might derive the greatest benefits from its use.In this paper, study on the determining of water productivity in artivicial lakes with morphoedaphic index analysis was showed.